PENERBITAN COVERNOTE TERHADAP OBJEK PERJANJIAN KREDIT - Andayani, Tri Astuti (Faculty of Law, University of Palembang, 2024)
Abstrak Covernote sebagai surat keterangan yang berisi kesanggupan notaris untuk melaksanakan apa yang diinginkan para pihak. Notaris mempunyai tanggung jawab penuh atas isi yang terdapat dalam suatu covernote. Covernote yang dibuat oleh notaris digunakan untuk dasar melakukan perjanjian kredit. Pada umumnya perjanjian kredit dan pengikatan jaminan dilakukan oleh notaris rekanan bank agar dibuat dalam bentuk akta autentik. Pada proses pengikatan jaminan hingga terbitnya sertifikat Hak Tanggungan biasanya membutuhkan waktu yang cukup lama, sehingga Notaris mengeluarkan covernote sebagai bentuk kesanggupan Notaris dalam menyelesaikan proses pengikatan jaminan. Atas dasar covernote tersebut, bank dapat mencairkan fasilitas kredit kepada debitur. Kata kunci : Notaris, covernote, pernjanjian kredit Abstract Covernote as a statement letter containing the notary ability to carry out what the parties want. The notary is fully responsible for the contents of the covernote. The covernote made by the notary is used as the basis for making a credit agreement. In general, credit agreements and collateral binding are carried out by a notary partner of the bank so that they are made in the form of an authentic deed. The process of binding collateral until the issuance of the Mortgage Certificate usually takes a long time, so the Notary issues a covernote as a form of the Notary ability to complete the collateral binding process. Based on the covernote, the bank can disburse credit facilities to the debtor. Keywords : Notary, Covernote, credit agreement